Human trafficking : The approach of the African Committee of Experts on the Rights and Welfare of the Child - Nanima, Robert; Kaime, Thoko (Intractable Problems of Human Rights, 2025)
This chapter examines the effectiveness of the African Children’s Committee in addressing child trafficking through a balanced approach. To support this argument, the authors present three key sub-arguments. First, they contend that the Committee’s normative framework provides sufficient guidance for tackling child trafficking. Second, they suggest that while the Committee’s institutional framework shows promise, it requires further strengthening to ensure its adequacy in addressing child trafficking. Lastly, the authors propose that an analysis of the Committee’s jurisprudential developments can inform future strategies for combating child trafficking. In passing, the approach of the African Children’s Committee requires improvement to make it more effective. A conclusion and recommendations follow.